Marx in the 21st century - Maffettone, Sebastiano, 1948- author.
1 online resource (ix, 118 pages).
Keywords: "This book introduces Marx as a political philosopher to the 21st-century reader. Comprehensive, accessible, and engaging in equal parts, it presents an unconventional reinterpretation of class struggle. Maffettone sheds light on Marx the individual, the intellectual, the political leader and icon, and links his lasting legacy to contemporary theories of justice. As one of the most prominent intellectual presences in history, Marx should not be read as a theorist of communism and socialism. Rather, he was, remains today and for the foreseeable future a radical critic of liberalism and capitalism. Within this innovative interpretive framework, he must be kept absolutely present in the analysis of contemporary politics. Under such premise, the volume explores Marx's life, his thoughts, his most important writings, his works on historical materialism and economic theory with a focus on concepts of labour, commerce, capitalism and surplus. The book also includes discussions on the Manuscripts of 1844, the Manifesto of 1848, a brief critical summary of Capital. A truly definitive work on the "phenomenon" that is Marx, this critical introduction will be of immense interest to scholars and researchers of political science, modern history, cultural studies, social anthropology, political philosophy, critical theory, justice, and economics, as well as appeal to the general reader"--